Steady and metastable cavitation in a converging-diverging nozzle - Gallman, Benjamin (Kansas State University, 2019)
While cavitation is usually avoided, it has useful engineering applications. Specifically, it can be used as to create cooling potential in a novel non-vapor compression refrigeration process. Cavitation occurs when the pressure of the working fluid (compressed liquid) drops below the saturation pressure. Since the cavitation (flash) results in an abrupt reduction in temperature, the working fluid can take in energy as heat from the surroundings during cavitation, which results in a cooling potential (refrigeration). In a converging-diverging nozzle, as the fluid passes through the throat the pressure decreases. If the pressure drops below the saturation pressure cavitation can occur. The current research focuses on measuring the pressure at the cavitation front, and the associated pressure distribution within the two-phase region in a converging diverging nozzle. A blow-down flow system was used to conduct measurements with water as the working fluid. The flow rate was measured with a rotameter and a Coriolis flow meter. The nozzle is a transparent 3D printed nozzle with an inlet diameter of 9.3 mm, throat diameter of 1.71 mm, and an outlet diameter of 9.3 mm. The upstream reservoir was kept at atmospheric pressure and was elevated above the level of the nozzle inlet. The downstream reservoir was evacuated to create a pressure difference that would drive fluid through the nozzle. The pressure distribution within the nozzle was measured with eight pressure transducers connected to the nozzle with 0.006” taps, and a high-speed camera was used to capture flow visualization. The pressure distribution was measured for steady cavitating flow at several back pressures, and during an increasing flow rate to capture pressure changes during cavitation initiation. These results give direct pressure measurements during cavitating flow, along with the accompanying flow visualization. They should prove useful for furthering understanding of the metastable fluid mechanics behavior of cavitating flows, and thereby contribute to the ability to maximize the cooling potential of the cavitation phenomena.
Keywords: Cavitation; Converging-Diverging Nozzle; Pressure Measurements; Flow visualization